2018
DOI: 10.1111/ecog.03561
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in kelp cover may threaten the recovery of California sea otters

Abstract: Despite more than a century of federal protection, the California sea otter Enhydra lutris nereis remains threatened under the U.S. Endangered Species Act (ESA), and the population has not appreciably expanded its range in two decades. Here, we examine a novel dataset of 725 sea otter live strandings from 1984-2015 to gain insights into demographic and environmental factors underlying threats to sea otter recovery. Using multinomial logistic regression to evaluate spatiotemporal patterns of stranding causes, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 66 publications
3
40
0
Order By: Relevance
“…Sea otters, however, have been slower to recover than pinnipeds and have reoccupied only 13% of their prior range (USFWS, ). Though the original causes of the sea otter population decline (hunting, fishery interactions) have been solved, the recent advent of mortalities from white shark bites suggests new threats to recovery (Nicholson et al, ; Tinker, Hatfield, Harris, & Ames, ).…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Sea otters, however, have been slower to recover than pinnipeds and have reoccupied only 13% of their prior range (USFWS, ). Though the original causes of the sea otter population decline (hunting, fishery interactions) have been solved, the recent advent of mortalities from white shark bites suggests new threats to recovery (Nicholson et al, ; Tinker, Hatfield, Harris, & Ames, ).…”
Section: Introductionmentioning
confidence: 99%
“…Though it is increasingly clear that shark bites on otters are incidental and nonconsumptive, the emerging impact of this dynamic is only recently explored. To begin, four studies (Ames, Geibel, Wendell, & Pattison, ; Ames & Morejohn, ; Nicholson et al, ; Tinker et al, ) have documented the extensive occurrence of stranded sea otters that bear bite wounds from white sharks, but have not (even partially) been consumed. Beyond this, an extensive study of white shark stomach contents (Klimley, ) revealed zero sea otter parts.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations